DETEKSI KRISTAL PROTEIN PADA ISOLAT BACILLUS SP. DENGAN PEWARNAAN COOMASSIE BRILLIANT BLUE - Siallagan, Maria Denada; Ekowati, Christina Nugroho; Sumardi, Sumardi; Rosa, Emantis (Universitas Jambi, 2020)
Bacillus is one of the genera of bacteria that has the potential to be developed in the field of biotechnology. Bacillus is able to produce protein crystals during the stationary phase in its life cycle. This protein crystal is a protoxin that is active will be pathogenic in insects. In this study, protein crystal staining was carried out using coomassie brilliant blue dye on the isolate of Bacillus sp. with isolate code B1, B2, and B3. Before being stained, the three isolates were bred on Nutrient Broth (NB) medium at pH 5, pH 7, and pH 9, then incubated for 72 hours. Based on research results, the three isolates were detected to produce protein crystals. Crystal protein of Bacillus sp. on media with a pH of 5 and pH 7 located at the end of the spore, while the protein crystal of Bacillus sp. isolate on media with a pH of 9 located on the outside of the spores.